Phosphorylation Regulates CIRBP Arginine Methylation, Transportin-1 Binding and Liquid-Liquid Phase Separation - Lenard, Aneta J.; Hutten, Saskia; Zhou, Qishun; Usluer, Sinem; Zhang, Fangrong; Bourgeois, Benjamin M. R.; Dormann, Dorothee; Madl, Tobias (Frontiers in Molecular Biosciences, 2021)
Arginine-glycine(-glycine) (RG/RGG) regions are highly abundant in RNA-binding proteins and involved in numerous physiological processes. Aberrant liquid-liquid phase separation (LLPS) and stress granule (SGs) association of RG/RGG regions in the cytoplasm have been implicated in several neurodegenerative disorders. LLPS and SG association of these proteins is regulated by the interaction of nuclear import receptors, such as transportin-1 (TNPO1) and post-translational arginine methylation. Strikingly, many RG/RGG proteins harbour potential phosphorylation sites within or close to their arginine methylated regions, indicating a regulatory role. Here, we studied the role of phosphorylation within RG/RGG regions on arginine methylation, TNPO1-binding and LLPS using the cold-inducible RNA-binding protein (CIRBP) as a model paradigm. We show that the RG/RGG region of CIRPB is in vitro phosphorylated by serine-arginine protein kinase 1 (SRPK1), and discovered two novel phosphorylation sites in CIRBP. SRPK1-mediated phosphorylation of the CIRPB RG/RGG region impairs LLPS and binding to TNPO1 in vitro and interferes with SG association in cells. Furthermore, we uncovered that arginine methylation of the CIRBP RG/RGG region regulates in vitro phosphorylation by SRPK1. In conclusion, our findings indicate that LLPS and TNPO1-mediated chaperoning of RG/RGG proteins is regulated through an intricate interplay of post-translational modifications.